Pendekatan Studi Islam: Macam-Macam Pendekatan Dilengkapi dengan Konsep Integrasi-Interkoneksi - Shofiyati, Arrum; Machali, Imam; Santosa, Sedya (AN NUR: Jurnal Studi Islam, 2024)
This article discusses various models of approaches to Islamic studies from various scientific perspectives, along with the concepts of integration-interconnection. Islamic studies from various scientific perspectives is one of the efforts to avoid the dimming of the existence of Islamic sciences along with the times. The purpose of this article is to: (1) find out various approaches to Islamic studies; and (2) know the concept of integration-interconnection and its implementation. This research method is literature study by collecting information related to the approach to Islamic studies and the concept of integration-interconnection from various journal articles, then analyzed using Miles & Huberman's interactive descriptive technique. The results of the research show that: (1) there are nine examples of approaches in Islamic studies with different scientific characteristics; and (2) the emergence of the concept of integration-interconnection which is an attempt not to carry out a dichotomy between general knowledge and religious knowledge. This concept is still being developed and perfected. Meanwhile, some of the obstacles to the development of integration-interconnection are due to the lack of human resources and the reality that does not support this integration-interconnection effort. Religious knowledge and general science are not designed to be combined or connected, so efforts to combine and connect the two are things that really need innovation and creation.